Prevalence and seasonal variation of ectoparasite in pigeon, Columba livia (Gmelin, 1789) of Dhaka, Bangladesh - Begum, Aleya; Sehrin, Sabrina (Bangladesh Journal of Zoology, 2012)
A total of 60 pigeons, Columba livia (25 males and 35 females) were examined for ectoparasites. All the birds were infected (100%) by 10 species of ectoparasites. The ectoparasite comprised lice: 60 (100%) Menopon gallinae, 28 (46.66%) Menacanthus stramineus, 43 (71.66%) Colpocephalum turbinatum, 60 (100%) Columbicola columbae, 31 (51.66%) Lipeurus caponis, 19 (31.66%) Goniocotes gallinae, 28 (46.66%) Chelopistes meleagridis; fleas: five (8.33%) Echidnophaga gallinacean; flies: 38 (63.33%) Pseudolynchia canariensis and eight (13.33%) of mites Dermanyssus gallinae. Serious damage was observed in wing feathers (31.74%). The females had a higher intensity (30.11) of infestation than the males (29.04). The ectoparasites were removed from the pigeons throughout the year. The overall intensity of infestation was highest during summer (40.69) and lowest during winter (21.94).